2007
DOI: 10.1097/01.tp.0000250485.53865.b8
|View full text |Cite
|
Sign up to set email alerts
|

Genomewide Expression Profiles of Rat Model Renal Isografts From Brain Dead Donors

Abstract: Because our experimental system is a good model of renal transplantation from brain dead or living human donors, our data may be useful for elucidating the pathologic processes involved and for identification of novel markers for graft dysfunction of renal transplantation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0
1

Year Published

2008
2008
2012
2012

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(23 citation statements)
references
References 24 publications
0
22
0
1
Order By: Relevance
“…This significant ischemic state is marked by elevated serum lactate levels (8)(9)(10). Appropriate donor management with hemodynamic stabilization after brain death toward normotensive levels limits organ dysfunction (8,11) and decreases the severity of the inflammatory response after brain death, which is demonstrated by a decrease in the number of CD8-positive cells in glomeruli and interstitium (9) (4), S100b (12,13), (14,15), complement activation and coagulation disorders (16 (12,13). The timeprofile of release suggests a role for S100b in delayed reparative processes.…”
Section: Induction Of Brain Death Leads To Hemodynamic Changesmentioning
confidence: 99%
See 2 more Smart Citations
“…This significant ischemic state is marked by elevated serum lactate levels (8)(9)(10). Appropriate donor management with hemodynamic stabilization after brain death toward normotensive levels limits organ dysfunction (8,11) and decreases the severity of the inflammatory response after brain death, which is demonstrated by a decrease in the number of CD8-positive cells in glomeruli and interstitium (9) (4), S100b (12,13), (14,15), complement activation and coagulation disorders (16 (12,13). The timeprofile of release suggests a role for S100b in delayed reparative processes.…”
Section: Induction Of Brain Death Leads To Hemodynamic Changesmentioning
confidence: 99%
“…However, when compared to organs retrieved from living donors, deceased donor kidneys have a significantly increased risk of delayed graft function and inferior long-term graft survival (1)(2)(3). The unphysiological state of brain death followed by preservation and ischemia/reperfusion-induced injury (4,5) will damage the kidney graft-to-be. After transplantation, the functioning nephron mass is reduced, which leads to exhaustion of the remaining nephrons due to hyperfiltration trying to meet the metabolic needs (6) and result in accelerated dysfunction (7).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies in rat and human transplant models have demonstrated the presence of an early-phase inflammatory process in response to brain death that is characterized by upregulation of adhesion molecules, cytokines, chemokines, and heat-shock proteins (HSP). 32,33 Recently, Smith et al 34 demonstrated the presence of HSP polymorphisms between white and black populations that are associated with altered mRNA and protein levels. Given the ability of HSP to protect against cell damage, some of these polymorphisms may reduce an individual's tolerance to the cellular insults associated with brain death.…”
Section: Clinical Research Wwwjasnorgmentioning
confidence: 99%
“…[213] IRI leads to organ dysfunction through induction of cytokines, generation of free radicals and activation of immunocompetent cells. [213,214] Endothelial cell dysfunction secondary to IRI is key in chronic allograft dysfunction in hearts, [215] lungs, [25] livers, [216] and kidneys. [217] Early injury to cells occurs as a direct result of ischaemia, with impaired oxygen delivery, altered energy metabolism and accumulation of waste products.…”
Section: Stage Three Of Potential Organ Injury: Ischaemia Reperfusionmentioning
confidence: 99%